2020
DOI: 10.18203/2349-2902.isj20204133
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study: combined irrigation of bupivacaine at the gallbladder fossa with infiltration at port site for postoperative pain relief after laparoscopic cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy is a well-established procedure for gallbladder disease. Pain in laparoscopic cholecystectomy is associated with multiple factors: somatic, visceral, and phrenic nerve irritation. Effective analgesic support should, therefore, be a multimodal approach following laparoscopic surgery for better patient compliance.Methods: A prospective, randomized observational study was undertaken at a tertiary research center for a period of two years (2018-2020). 160 patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…7 Local tissue infiltration with local anesthetics is one of the simple, yet effective, techniques to prevent and control pain in first 24 hours. This response to intra-peritoneal local anesthetics is mediated by local peritoneal effects rather than by systemic absorption and has a lot of other advantages like simplicity, safety and low cost 8 . Bupivacaine has the longest half life of the generally used local anesthetic drugs in modern-day anesthesia practices.…”
Section: Introductionmentioning
confidence: 99%
“…7 Local tissue infiltration with local anesthetics is one of the simple, yet effective, techniques to prevent and control pain in first 24 hours. This response to intra-peritoneal local anesthetics is mediated by local peritoneal effects rather than by systemic absorption and has a lot of other advantages like simplicity, safety and low cost 8 . Bupivacaine has the longest half life of the generally used local anesthetic drugs in modern-day anesthesia practices.…”
Section: Introductionmentioning
confidence: 99%
“…Bile leakage due to rupture of gall bladder contributes to 7% -21.77% 4,5,7 according to most studies with conversion of laparoscopic into open cholecystectomy. Studies showed stone spillage with its retrieval from the fossa of gall bladder can be done by irrigation or be mopping with surgical gauze 7,8 . Study by Rao et al has found 9.34% spilled gall stones intraoperatively due to gall bladder perforation 8 and is avoidable by mopping or irrigation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed stone spillage with its retrieval from the fossa of gall bladder can be done by irrigation or be mopping with surgical gauze 7,8 . Study by Rao et al has found 9.34% spilled gall stones intraoperatively due to gall bladder perforation 8 and is avoidable by mopping or irrigation techniques. Also patients can be monitored postoperatively with signs of persistent pain reported to be 18.64% compared to control group 5.08% in study by Pankaj et al different studies have been done and has found that retrieval of stones is possible in 63% of cases only 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation